Implementation of Tax in Indonesia from the Perspectives of Muhammadiyah and NU - Putra, Budi Jaya; Tri Wibowo, Wahyu (JAMPE (Journal of Asset Management and Public Economy), 2025)
Taxes remain a widely-discussed topic. It is because taxes are not only limited to state finances but also play a crucial role in a country’s development. This study examines the implementation of taxes (Tax Law, Education Tax, and Tax Amnesty) in a country from the perspectives of Muhammadiyah and Nahdlatul Ulama (NU). This study aims to provide scientific contributions and fill the gap regarding the role of Islamic organizations, specifically Muhammadiyah and NU, in Indonesia, in terms of tax implementation. This study employs the library method as its research approach. The method involves collecting information from laws and regulations, as well as books and articles related to state regulations and the statements or decisions of organizations. The results of the study indicate that Muhammadiyah and NU share the same view regarding tax law. They consider taxes mandatory. For the VAT on education, Muhammadiyah and NU disagree. It is because they also consider it to be contrary to the spirit of Pancasila and the welfare of the people. Furthermore, Muhammadiyah agrees with tax amnesty. However, Muhammadiyah continues to provide input and suggestions to the government. On the other hand, NU has not reached an agreement on the tax amnesty law. Upon examining previous decisions, it was found that NU did not permit Tax Amnesty. This study contributes to the formulation of more inclusive and equitable public policies by integrating the religious perspectives of Muhammadiyah and NU on the implementation of taxes in Indonesia. Thus, it will increase the legitimacy, compliance, and trust of the Muslims in the national taxation system.